Efficacy of Anthrax Spore Vaccine on Sheep: A Spectroscopic Approach - Rajalakshmi, A.; Gunasekaran, S.; Renugadevi, T.S. (Asian Journal of Chemistry, 2010)
In this work, normal healthy pre-vaccinated blood samples (zero day) and post vaccinated (7th, 14th and 21st day after vaccination) blood samples are analyzed by employing Fourier transform infrared spectroscopic techniques (FTIR). The variation in peaks is expected due to the production of antibodies in the animal. The internal standards among the application peaks are calculated. Among the various techniques to study the antibody production, ELISA (enzymelinked immuno sorbent assay) is considered to be a better one, which can be done only in sophis-ticated laboratories. Spectral study can be taken as an alternate method and it can be compared with ELISA in future. Spectroscopic methods of blood analysis have an alternate technique to the clinical methods since they require fewer samples and provide more information.